Effect of Anredera cordifolia (Ten) Steenis Leaves Ethanol Extract in suppressing Brown PlantHopper (Nilaparvata lugens Stal.) Populations on Rice Plant - Martua Suhunan Sianipar; Tarkus Suganda; Azhhar Hadyarrahman (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2020)
The Brown Planthopper (Nilaparvata lugens Stal.) is one of the pests that often causes rice crop failure in rice. One way to control N. lugens pests is to use of botanical insecticide. The purpose of this experiment is to study the effect of A. cordifolia leaves ethanol in suppressing N. lugens populations. The experiment used a Randomized Block Design (RDB) with 8 treatments and 4 replications. The A. cordifolia leaves ethanol extract concentration tested in this experiment consisted of 0,5%; 0,75%; 1%; 1,5%; and 2%. The results of the experiment showed that the ethanol extract of binahong leaves with a concentration of 1%, 1.5% and 2% cause mortality of N. lugens by 52.50%, 56.25%, and 61.25% on the 14th day after application. Based on the results of this experiment, the ethanol extract of A.cordifolia leaves was not effective against N. lugen.